A BRIEF REVIEW OF SIYASAH SYAR'IYYAH ON THE ROLE OF THE MINISTRY OF LAW AND HUMAN RIGHTS IN DEALING WITH OVER-CAPACITY OF PRISONERS IN CORRECTIONAL INSTITUTIONS CLASS II A SUNGGUMINASA - Indah Sari B (Jurnal Al Tasyri'iyyah, 2025)
This study aims to discuss a brief review of Siyasah Syar'iyyah on the role of the Ministry of Law and Human Rights in dealing with overcapacity of prisoners in correctional institutions class II A Sungguminasa. This study is qualitative in nature. The research design is field research. The results of this study show that the strategies implemented by the Sungguminasa Class II A Correctional Institution to deal with overcapacity include programs such as parole, conditional leave, remission, and home assimilation. Home assimilation was previously in effect but has since been discontinued. This shows that there are benefits. This is an indicator of alignment with Siyasah Syar'iyyah. One inmate complained that physical and psychological health problems could occur as a result of overcapacity. In addition, it also makes it difficult to move around and could lead to conflict. This indicates a contradiction with the benefits. It is an indicator of a lack of alignment with Siyasah Syar'iyyah. The Ministry of Law and Human Rights, in this case the Sungguminasa Class IIA Correctional Institution, must remain committed and strive to address overcapacity by proposing more effective programs while implementing legal programs. This is because the existing programs still show a contradiction with the benefits. If not, it means ignoring the benefits that indicate a lack of alignment with Siyasah Syar'iyyah.